Patients with carotid atherosclerosis who underwent or did not undergo carotid endarterectomy: outcome on mood, cognition and quality of life. Issue 1 (December 2015) - Carta, Mauro; Lecca, Maria; Saba, Luca; Sanfilippo, Roberto; Pintus, Elisa; Cadoni, Michela; Sancassiani, Federica; Moro, Maria; Craboledda, Davide; Lo Giudice, Chiara; Finco, Gabriele; Musu, Mario; et al.
Abstract Background To compare the six-month outcome on mood, cognition and quality of life (QoL) in patients with severe carotid atherosclerosis (CA) who underwent carotid endarterectomy (CEA) with subjects who refused treatment. Methods Cohort study on consecutive inpatients with CA (stenosis ≥ 50 %) (N =  46; age 72.56 ± 7.26; male 65.2 %). Intervention cohort: subjects who decided to undergo CEA (N =  35); Control cohort patients who refused CEA (N =  11). DSM-IV-Psychiatric diagnosis made by clinicians using interviews, QoL measured by Short Form Health Survey (SF-12); cognitive performance by WAIS Intelligent Coefficient (IC). Results The study showed a better improvement during six months in Overall IC, Performance IC and Verbal IC in the group that underwent CEA. QoL in the two cohorts did not reach statistical significance. Percentages of patients who improved in the CEA group were significantly higher with regard to Overall and Verbal IC scores, and at the limits of statistical significance in Performance IC. The differences of subject with improvement in SF-12 score in the two groups did not reach statistical significance. Ages below 68 were found to be determinant of a good outcome in Overall IC score. Limit: study conducted with a small sample size. Conclusions Patients with severe carotid atherosclerosis who underwent CEA enhanced their cognitive performance.